Story of Jumbo book cover - Edwards, W.F.L. (Tufts Archival Research Center, 2007)
9 1/4 x 7. This book cover illustration is from W.F.L. Edwards, "The Story of Jumbo" (St. Thomas [Ont.] : Sutherland Press, c.1935).